Pengembangan Modul Dasar Instalasi Listrik di Jurusan Pendidikan Teknik Elektro Universitas Negeri Manado - Hizkia Marfel Mokalu; Billy M.H. Kilis; Viverdy F.C. Memah (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
The purpose of this research is to develop two basic modules in electrical installation courses and second, to determine the feasibility level of basic modules in electrical installation courses. Learning modules can train students to be able to learn independently. Because the relevant modules have not been found related to the basic installation planning in the PTE UNIMA department. Therefore, researchers develop learning modules as one of the effective means used in studying the material, so that it is expected to increase knowledge, as well as ability to think. The research method used is Research and Development with a 4D development model developed by S. Thiagarajan. The instrument used is a questionnaire with a Likert scale of 4 for experts and for students. The validity of the instrument used is based on the opinion of experts (Expert Judgment). The research subjects are media experts, material experts, and students. This data collection uses a questionnaire that is created and distributed using a google form to 2 expert lecturers and to students. The feasibility level of the basic module of electrical installation planning carried out by material experts obtained a score of sixty-four out of a maximum score of ninety-two with the